A Hayekian View on European Union - Veronica Coca (CES Working Papers, 2010)
The aim of this paper is to develop some general Hayek's ideas on the European project. Hayek demonstrated and analyzed the presence of two types of social order - a spontaneous order and a built one. Spontaneous order is a feature of society and economic development around a principle of human action coordinator. European project represents the spontaneous order through the founding principles of the four freedoms - free movement of persons, goods, services and capital. With many regulations, bureaucracy, this order is closer to the order constructed by that social engineering. Following Hayek's ideas I tried to emphasize some issues at European level and to achieve a correlation with the european reality and Hayekian theory.
Keywords: 330; spontaneous order; rule of law; freedom; institutions